2000
DOI: 10.1111/j.1708-8240.2000.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of Compomer after Immersion in Various Media

Abstract: Purpose: The purpose of this study was to evaluate the effect of various media on the color stability of compomer and to compare these results to those of other materials that could be used in similar clinical circumstances. Materials and Methods:In this test, six materials (shade A2) were used: four compomers (Dyract, Compoglass F, Xeno, F2000), one composite resin (Clearfil AP-X), and one resin-modified glass ionomer cement (Fuji I1 LC). There were four test solutions: one alcoholic (whiskey), two low pH sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
1
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 13 publications
4
130
1
9
Order By: Relevance
“…These results clearly demonstrated that a distinctive relation existed between the filler content of flowable resins and their surface roughness. This relation has been clarified in previous research 6,7,13) . In the present study, flowable resins with lower filler contents were shown to exhibit a higher degree of surface roughness (Table 2).…”
Section: Relation Between Filler Content and Surface Propertiesmentioning
confidence: 99%
“…These results clearly demonstrated that a distinctive relation existed between the filler content of flowable resins and their surface roughness. This relation has been clarified in previous research 6,7,13) . In the present study, flowable resins with lower filler contents were shown to exhibit a higher degree of surface roughness (Table 2).…”
Section: Relation Between Filler Content and Surface Propertiesmentioning
confidence: 99%
“…The differences of color were given by ΔE*, which was obtained using the following equation (11): √ΔE*= (ΔL*) 2 + (Δa*) 2 + (ΔB*) 2 .…”
Section: Methodsmentioning
confidence: 99%
“…If the color of the composite changes with time, its main advantage, esthetics, is lost. For this reason, studies have been performed with the goal of assessing the maximum color stability of composites through time (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Color change in Dentistry has been expressed quantitatively, based on the CIE L*a*b* system. This system provides a summarizing measure (ΔE*) that represents the overall color change, and may be classified into three distinct intervals, considering the ability of the human eye to recognize differences in colors: a ΔE*<1 is considered imperceptible by the eye, while 1 <ΔE*< 3.3 is considered visible only to a skilled person and ΔE* > 3.3 is easily detected by anyone, characterizing the color change of a restoration as clinically unacceptable 7,8 . Other studies have confirmed the color changing effect of several extrinsic pigments from dietary sources, including grape juice, red wine and coffee 4,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%